2002
DOI: 10.1177/01945902024004010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship as an Inherent Component in Healthy Women’s Fatigue

Abstract: The notion of fatigue has remained ambiguous despite more than 100 years of study. Fatigue is recognized as subjective in nature, and it is studied and clinically managed as primarily intrapersonal in scope, with treatment approaches often based in an established, if unfounded, hierarchy of assumptions. When a physiologic cause for fatigue is not identifiable, fatigue complaints often are considered illegitimate. This article builds on data from the literature and from the author's previous work in women's fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…32,33 Regarding social factors, previous studies have yielded compelling evidence demonstrating a notable correlation between social support and interaction and fatigue among older adults. 34,35 It has also been suggested that social engagement can indirectly mitigate the risk of sarcopenia by affecting physical, oral, psychological, and nutritional status. 36 From this perspective, the various factors discussed in this study are appropriate for frailty prevention in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Regarding social factors, previous studies have yielded compelling evidence demonstrating a notable correlation between social support and interaction and fatigue among older adults. 34,35 It has also been suggested that social engagement can indirectly mitigate the risk of sarcopenia by affecting physical, oral, psychological, and nutritional status. 36 From this perspective, the various factors discussed in this study are appropriate for frailty prevention in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the current findings revealed a significant relationship between fatigue and social support which is a situational factor (i.e., social network and social support). Previous studies [26][27]51] focused on only healthy and young-old adults. This finding extends previous research noting that social support had a significant effect on fatigue for oldest-old adults.…”
Section: Discussionmentioning
confidence: 99%
“…This is another important finding of this study suggesting the inclusion of situational factors for fatigue with oldest-old participants. Most studies that investigated the influences of social support or social networks on fatigue included only younger and healthy participants [26,27] . Another significant aspect of this study is the focus on advanced old age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations